Psychological aspects of organization and formation of correctional habilitation space for young children (Actual Problems of Psychology in Educational Institutions, 2021)
The article highlights the psychological aspects of medical sociopsychological rehabilitation of young children with special educationalneeds. The importance of a balanced harmonious impact on the psyche of achild as a future citizen of modern society is noted. The author pays specialattention to the development of sensorimotor, psychomotor neoplasmson the basis of compensatory properties of higher mental functions. Thesignificance of the simulated environment, which influences the sensations ofdifferent modality, has been determined. The author cites the results of anempirical study of the behavioral reactions of pupils of the Children’s Home.The relevance of the systemic modeling of the correctional environment asa factor influencing the quality of certainty of the child’s feelings has beenproved.
Keywords: habilitation, rehabilitation, compensatory properties, simulated environment, perception, modality